Endometrial lymphoid tissue: an immunohistological study. Issue 6 (June 1985) - Morris, H; Edwards, J; Tiltman, A; Emms, M
Abstract : Lymphoid tissue of the endometrium was analysed by histological, immunohistological, and electron microscopical methods in 10 healthy uteri. A panel of monoclonal antibodies recognising macrophages (OKMI), HLA-DR antigen, B lymphocytes, T lymphocytes and their subsets, and dendritic reticulum cells was used in a two stage indirect immunoperoxidase labelling technique. Endometrial lymphoid tissue showed a remarkably consistent pattern of labelling in all cases. Lymphoid tissue was present in three sites: namely, (i) intraepithelial lymphocytes (predominantly T lymphocytes with occasional macrophages) associated with periglandular and sub-epithelial HLA-DR+, OKMI+ macrophages; (ii) interstitial lymphocytes and macrophages; (iii) lymphoid aggregates in the stratum basalis. These were composed mainly of T lymphocytes with a few B lymphocytes. Dendritic reticulum cells were found in those occasional lymphoid aggregates in which germinal centres were present. These features suggest that endometrial lymphoid tissue has many of the hallmarks of mucosal associated lymphoid tissue as found elsewhere in the body–for example, the bronchus and intestine. Endometrial lymphoid tissue appears to be unique, however, in that most of the stratum functionalis in which it is situated shows cyclical shedding during the menstrual cycle.